Co(ii) and Zn(ii) pyrazolyl-benzimidazole complexes with remarkable antibacterial activity. (14th January 2020) - Chkirate, Karim; Karrouchi, Khalid; Dege, Necmi; Kheira Sebbar, Nada; Ejjoummany, Abdelaziz; Radi, Smaail; Adarsh, N. N.; Talbaoui, Ahmed; Ferbinteanu, Marilena; Essassi, El Mokhtar; Garcia, Yann
Abstract : Three pseudopolymorphs based on a coordination complex of a pyrazolyl-benzimidazole ligand have been synthesized and characterized by single crystal X-diffraction, and showed remarkable antibacterial properties. Abstract : Three mononuclear coordination complexes of 1-butyl-2-((5-methyl-1 H -pyrazol-3-yl)methyl)-1 H -benzimidazole (L ), namely [CoL]Cl2 (C1 ), [Co2 L2 ]Cl2 ·H2 O (C2 ) and [Zn2 L2 ]Cl2 (C3 ), have been synthesized and characterized spectroscopically. Their single-crystal X-ray diffraction analysis revealed that C1 and C2 display pseudopolymorphism. The presence of N–H⋯Cl and C–H⋯Cl hydrogen bonding in the crystal structure of C1 and C3 assists the formation of a 2D hydrogen bonded sheet and orthogonal packing [2D sheet + a pair of 1D chains], respectively, leading to supramolecular structures. A combination of N–H⋯Cl, C–H⋯Cl, O–H⋯Cl, and C–H⋯O interactions results however in a 2D corrugated hydrogen bonded sheet with inclusion of water molecules in C2 . Hirshfeld surface analysis confirms that hydrogen bonding and π-stacking contacts stabilize the crystal structures. These metal complexes display good performance towards their antimicrobial activity against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus . In particular a normalized minimum inhibitory concentration as low as 6.25 μg mL −1 for the bacterial strains was recorded for C2 . Its structure–bioactivity correlation is discussed in detail.